Lavender Marriage and the Failure of Maqasid al-Usrah: Sexual Orientation Deception and the Violation of Wives’ Rights - Mufatihatuttaubah Rorom Ika Putri; Siti Amiratul Adibah; Anisah Nayla Maghfiroh (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2026)
The phenomenon of lavender marriage gives rise to significant legal ambiguity. A lavender marriage is a marriage used to conceal one’s sexual orientation from an unsuspecting spouse. Although such marriages formally satisfy the legal and religious requirements for marriage, they involve deception through the concealment of the husband’s sexual orientation. This study examines the extent to which lavender marriages fulfil the objectives of marriage within the Maqasid al-Usrah framework, focusing on their impact on the wives’rights, the validity of the practice, and the relevance of Maqasid al-Usrah in addressing these issues. This study employs a descriptive-qualitative method using a netnographic approach, through the analysis of podcasts as digital cultural artefacts representing the experiences of victims of ‘lavender marriages’. The data sources consist of podcasts from the YouTube channels of Deddy Corbuzier, Denny Sumargo, and Richard Lee, selected for their direct involvement of the interviewees and relevance to the research focus. The findings reveal that lavender marriages fail to fulfil the core objectives of Maqasid al-Usrah because they undermine honesty within marital relationships and fail to provide tranquillity and mutual trust between spouses. The practice also weakens family functions by obstructing reproductive rights, diminishing moral responsibility, and reducing marriage to an instrument of social concealment. As a solution, this study recommends amending Indonesia’s Marriage Law to explicitly recognise the fraudulent concealment of sexual orientation as a valid ground for annulment or divorce. It further encourages judges to adopt a justice-oriented approach that prioritises substantive fairness for wives who were deceived regarding their spouse’s sexual orientation.